Literasi Aspek Pemasaran pada UKM “Nabil Collection” - Benny Diah Madusari; Arum Ardianingsih; Dwi Edi Wibowo (Jurnal SOLMA, 2021)
Background: “Nabil Collection” are SMEs affected by restrictions on activities outside the home. SME “Nabil Collection” has been selling its shirt products conventionally so that when there is a policy of limiting activities outside the home, the sales of their products decrease. This literacy is carried out so that the SME “Nabil Collection” has the ability to do product packaging, the importance of trademarks and choose the right marketing media according to the product market target. Method: Literacy for SME owners “Nabil Collection” by providing modules on the marketing aspects of shirt products. Result: increased knowledge of “Nabil Collection” SME owners about product packaging, trademarks and online marketing media with social media. Conclusions: This literacy aspect of marketing increases the knowledge of “Nabil Collection” SME owners knowing more creative product packaging, realizing the importance of trademarks, more competitive shirt product prices and trying alternative social media-based marketing media to increase product sales during the time of restrictions on activities outside the home.